The Role of Islamic Education Teachers in Instilling Ethical Values of Islamic Social Interaction and Communication in Junior High Schools - Yusuf, M.; Putri, Fitriani Dela (Ahlussunnah: Journal of Islamic Education, 2025)
The development of information technology and digital media has influenced students' communication and social interactions, leading them to increasingly deviate from Islamic ethical values. This situation emphasizes the importance of Islamic Religious Education teachers in fostering students' morals at school, particularly in maintaining good communication and social interaction. This study aims to describe the role of Islamic Education teachers in instilling Islamic ethical values in social interactions and communication at Junior High School 1 Ulakan Tapakis, Indonesia and analyze the supporting and inhibiting factors. The method used is descriptive qualitative with data collection techniques such as observation, interviews, and documentation. The results show that Islamic Education teachers carry out their role through role models, habituation, and integration of Islamic values in learning. The strategies implemented include lectures, discussions, communication etiquette simulations, and the wise use of technology. This guidance has an impact on improving politeness, the ability to maintain good language, and reducing negative social behavior among students. Therefore, the role of Islamic Education teachers is very significant in strengthening character education for the younger generation in the digital era.